2009
DOI: 10.1103/physrevb.79.224107
|View full text |Cite
|
Sign up to set email alerts
|

Structural phase transitions of sodium nitride at high pressure

Abstract: The structural evolution of recently characterized sodium nitride Na 3 N as a function of pressure was investigated at room temperature by the angle-dispersive powder x-ray diffraction in a diamond-anvil cell up to 36 GPa. The rather open cubic anti-ReO 3 -type structure stable at ambient pressure is followed by a series of four high-pressure modifications. Along the route, the coordination number for the nitride anion increases from 6 in Na 3 N-I to 8 in hexagonal Li 3 N-type Na 3 N-II, 9 in orthorhombic anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
22
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 36 publications
5
22
1
Order By: Relevance
“…Sodium nitride Na 3 N. Another deceptively simple chemical system where a successful synthesis followed the prediction is Na 3 N. 8 In several studies Schö n et al, 2000Schö n et al, , 2001b, the enthalpy landscapes of all alkali nitrides M 3 N (M = Li, Na, K, Rb, Cs) were explored with simulated annealing and the threshold algorithm for a wide range of pressures. Furthermore, at intermediary pressures another modification exhibiting the YF 3 type was observed (Vajenine et al, 2008(Vajenine et al, , 2009) that resembles several structures found as local minima on the enthalpy landscapes of the alkali nitrides. Fig.…”
Section: Theoretical Applicationsmentioning
confidence: 54%
See 2 more Smart Citations
“…Sodium nitride Na 3 N. Another deceptively simple chemical system where a successful synthesis followed the prediction is Na 3 N. 8 In several studies Schö n et al, 2000Schö n et al, , 2001b, the enthalpy landscapes of all alkali nitrides M 3 N (M = Li, Na, K, Rb, Cs) were explored with simulated annealing and the threshold algorithm for a wide range of pressures. Furthermore, at intermediary pressures another modification exhibiting the YF 3 type was observed (Vajenine et al, 2008(Vajenine et al, , 2009) that resembles several structures found as local minima on the enthalpy landscapes of the alkali nitrides. Fig.…”
Section: Theoretical Applicationsmentioning
confidence: 54%
“…5.1.2. Experimentally, the ReO 3 type (Fischer & Jansen, 2002b), the Li 3 N, the Li 3 P and the Li 3 Bi structure types (Vajenine et al, 2008(Vajenine et al, , 2009) have all been synthesized, the latter three using high-pressure experiments starting from the ReO 3 type. This resulted in a large number of structure candidates, including, for example, the Li 3 N, the Li 3 P, the Li 3 Bi, the AuCu 3 , the Al 3 Ti, the ReO 3 and the UO 3 structure types, plus many previously unknown structure types.…”
Section: Theoretical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…8) have recently been realized [83]. This impressively documents the strength of our new rational way for solid-state synthesis, and this result has attracted a lot of interest, which in part arose because of generations of solid-state chemists having tried in vain to synthesize Na 3 N.…”
Section: Experimental Verificationsmentioning
confidence: 90%
“…Since the computational efforts to be made at exploring configuration spaces of significant size are huge, in the beginning, we based the total energy calculations on computationally "cheap" empirical two-body potentials. [2a-d] In spite of this approximation, the results have been quite promising, and the feasibility of the concept has been proven convincingly and validated experimentally at the example of the alkali metal nitrides [13][14][15] and the lithium halides. [16,17] However, the two-body potentials used, consisting of a Coulombic and a Lennard-Jones term, give predominantly ionic structures and are not suitable to address, for example, configurations containing homoatomic bonds.…”
mentioning
confidence: 98%